How are Critical Thinking Skills on Indonesian Language Learning on AKM Literacy Based? - Nugraha, Mia Uswa; Apriliya, Seni; Nursofa, Risma; Dinaryanti, Dina; Purnamawati, Eva; Rahmi, Hestika Asri (Indonesian Journal of Primary Education, 2024)
Critical thinking skills are needed by students in Indonesian language learning in elementary schools as a provision in solving problems in their lives later. This study aims to provide knowledge to educators and other researchers about the current conditions related to critical thinking skills possessed by grade VI students in elementary schools in Indonesian language learning in terms of assessment instruments adapted from AKM literacy questions. This study uses a quantitative design used to measure the extent of critical thinking skills in the form of literacy test questions adapted from AKM questions and then modified so that they contain indicators of critical thinking skills and indicators of AKM literacy questions. And qualitative design to process data from ethnographic studies through analysis of interviews and observations used to explore the causes of low critical thinking skills. The results showed that critical thinking skills in grade VI students were still in sufficient criteria. Of the six FRISCO critical thinking skills indicators, only the focus, inference, and sittuation indicators are included in the good criteria and the reason, clarity, and overview indicators are still included in the sufficient criteria, so that the final average of the six critical thinking skills indicators is included in the sufficient criteria. This is due to students reading the question no matter what. This is because students read the questions incompletely so that they do not understand the questions asked. The length of the reading contained in the story causes learners to find it difficult to find information that is really important. Learners only focus on the first sentence in each paragraph with the aim that the question can be done quickly. Therefore, it is necessary to familiarize Indonesian language learning using assessment instruments based on AKM literacy questions so that students are accustomed to thinking critically.